Tobacco TTG2 regulates vegetative growth and seed production via the predominant role of ARF8 in cooperation with ARF17 and ARF19. Issue 1 (December 2016) - Ge, Jun; Li, Baoyan; Shen, Dan; Xie, Junyi; Long, Juying; Dong, Hansong
Abstract Background Plant TRANSPARENT TESTA GLABRA (TTG) proteins regulate various developmental activities via the auxin signaling pathway. Recently, we elucidated the developmental role of tobacco (Nicotiana tabacum L.) NtTTG2 in association with 12 genes that putatively encode AUXIN RESPONSIVE FACTOR (ARF) proteins, including NtARF8, NtARF17, and NtARF19. Here we show that NtTTG2 regulates tobacco growth and development by involving theNtARF8, NtARF17, andNtARF19 genes, with theNtARF8 gene playing a predominant contribution. Results Independent silencing of theNtARF8 gene more strongly repressed tobacco growth than silencing theNtARF17 orNtARF19 gene and more effectively eradicated the growth enhancement effect ofNtTTG2 overexpression. In contrast, plant growth was not affected by silencing additional nineNtTTG2 -regulatedNtARF genes. In double and triple gene silencing combinations, silencing theNtARF8 gene was more effective than silencing theNtARF17 orNtARF19 gene to repress growth as well as nullify growth enhancement. Therefore, theNtARF8 predominantly cooperated with theNtARF17 andNtAFR19 of theNtTTG2 functional pathway.NtARF8 also contributed to NtTTG2-regulated seed production as concurrentNtTTG2 andNtARF8 overexpression played a synergistic role in seed production quantity, whereas concurrent silencing of both genes caused more severe seed abortion than single gene silencing. In plant cells, the NtTTG2 protein facilitated the nuclear import of NtARF8 as well as increased its function as a transcription activator. Conclusions NtARF8 is an integral component of the NtTTG2 functional pathway, which regulates tobacco growth and development.